216 Anti-tumor activity of iosH2 by blocking LILRB2 receptor signalling. (9th November 2020) - Belaunzaran, Osiris Marroquin; Rafiei, Anahita; Kumar, Anil; Kolibaba, Julia; Vogt, Lorenz; Smith, Sean; Renner, Christoph
Abstract : Background: The human leukocyte immunoglobulin-like receptor family B (LILR B) acts as check point blockade of the innate immune system by inhibiting leukocyte activation through SHP phosphatase recruitment. Some of the physiological ligands include classical HLA class I molecules, including beta-2-microglobulin (B2M) free open conformers (OC). Natural HLA-OC expression is known from autoimmune disease leading to immune activation by pleiotropic effects since they bind to LILRB and KIR family members reducing Treg and MDSC numbers and increased effector T-cell and NK-cell activation, respectively. We have generated an IgG4-HLA-57 open conformer (OC) molecule (iosH2) with high affinity for LILRB molecules and demonstrate its anti-cancer activity in vitro and in vivo. Methods: iosH2 was produced by transient gene expression in CHO cells and purified by standard chromatography. Affinity of iosH2 binding was quantified by ELISA and SPR analysis. HLA-G mediated signaling and competition was assessed using functional cell lines. Effect of iosH2 on activation of SHP1/2 was assessed using Western Blot. Functional assays including in vitro polarization and phagocytosis potential of primary macrophages was assessed by flow cytometry in the presence of iosH2 or isotype control. Effect of iosH2 on T cell activation was evaluated in co-cultures of cancer and T cells. Mouse models were used to assess in vivo activity. Results: iosH2 binds to LILRB2 with high affinity and blocks the activation of HLA-G. In addition, iosH2 blocks receptor-mediated activation of SHP1/2. iosH2 promotes a shift from M2 to M1 macrophages with enhanced tumor cell phagocytosis in vitro. iosH2 enhances activation and killing potential of T cells in cancer cells and T cells co-culture assay. iosH2 exerts therapeutic efficacy in mouse transgenic (melanoma) and different syngeneic tumor models (e.g. pancreatic, colon and breast cancer) as monotherapy. Moreover, it acts synergistically in vivo with PD1 blocking antibodies achieving long-term tumor control. Ex vivo tumor sample analysis demonstrates a significant reduction of MDSC and Tregs and a shift towards an activated inflammatory M1 macrophage phenotype. Loss of MDSC functionality was paralleled by enhanced CD8+ T cell expansion and activity. Conclusions: iosH2 binds to LILRB2 with high affinity, restores immune cell function in vitro and demonstrates anti-tumor activity in different in vivo mouse models. In addition, it acts synergistically in vivo with PD1. iosH2 is a first-in-class OC therapeutic with robust anti-tumor activity by promoting key components of the innate immune system. Clinical development is under way and phase I trial in preparation.